2022
DOI: 10.3389/fpsyg.2022.1024250
|View full text |Cite
|
Sign up to set email alerts
|

Chinese English teachers’ occupational intention during distance education: The role of burnout and job-related stress

Abstract: Since turnover intention has a negative impact on teachers’ productivity, a bulk of educational research has studied the personal, organizational, and emotional predictors of this construct. Nevertheless, the predictive function of burnout and job-related stress as two emotional factors has been less attended to by scholars. To address this gap, the current empirical study explored the role of burnout and job-related stress in Chinese English teachers’ turnover intention during distance education. In doing so,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Most quantitative studies on job burnout of EFL teachers in China are based on MBI (Zhang, 2012(Zhang, , 2022Hu, 2014;Li, 2016;Fan et al, 2017;Li and Zhang, 2020;Bing et al, 2022;Ding and He, 2022;Song, 2022;Yang, 2022). Some empirical studies revised some items of MBT and added some items to highlight China's national conditions and cultural specificity (Chen and Lin, 2008;Xu, 2010;Yao, 2011;Tang and Zhao, 2013;Tang, 2020).…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Most quantitative studies on job burnout of EFL teachers in China are based on MBI (Zhang, 2012(Zhang, , 2022Hu, 2014;Li, 2016;Fan et al, 2017;Li and Zhang, 2020;Bing et al, 2022;Ding and He, 2022;Song, 2022;Yang, 2022). Some empirical studies revised some items of MBT and added some items to highlight China's national conditions and cultural specificity (Chen and Lin, 2008;Xu, 2010;Yao, 2011;Tang and Zhao, 2013;Tang, 2020).…”
Section: Empirical Studiesmentioning
confidence: 99%
“…The conservation of resources theory expresses that individuals with ample resources can acquire more resources and are less vulnerable to resource loss. In daily work, Zhao et al (2020), primary school teachers undertake a heavy teaching and student management workload and thus must instill many internal and external resources. Some researchers like Kosir et al (2015) & Bottiani et al (2019) state that when teachers face strain from numerous factors, such as workload, test pressure, and student administration, it is likely to result in powerlessness and even frustration due to limited resources, their studies have indicated positive relationships between occupational stress and teacher burnout.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, primary school teachers meet selfdevelopment stress, such as low salaries and limited development prospects. Face with many factors, coupled with the concern that their professional effort is undeserved, the reward received results in more severe job stress among primary school teachers (Qi et al, 2014;Zhao et al, 2020). Thus, this research investigated the mentioned gaps to ascertain the current situation of public elementary teacher work stress and the possible influence of such intense work stress on teacher burnout.…”
Section: Introductionmentioning
confidence: 99%